Rate of Snow Accumulation Determined from Oxygen Isotope and Stratigraphic Analyses of the Core from Mizuho Station, East Antarctica (Extended Abstract) - Kato, Kikuo; Watanabe, Okitsugu; Satow, Kazuhide; Okuhira, Fumio (1979)
P(論文) departmental bulletin paper